2012
DOI: 10.1055/s-0031-1299574
|View full text |Cite
|
Sign up to set email alerts
|

Renal Graft Outcome in Combined Heart–Kidney Transplantation Compared to Kidney Transplantation Alone: A Single-Center, Matched-Control Study

Abstract: Our results with excellent long-term graft function and survival after combined HKTx indicate that this procedure is a valuable option for a growing number of patients suffering from coexistent cardiac and renal failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
3
0
1
Order By: Relevance
“…As has been subsequently shown in other studies, [12][13][14] combined transplantation reduced the prevalence of cardiac allograft rejection. Although the putative mechanism of reduced allograft rejection (both kidney and heart) remains unclear, it is speculated that the organ combination induces immunogenic tolerance.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As has been subsequently shown in other studies, [12][13][14] combined transplantation reduced the prevalence of cardiac allograft rejection. Although the putative mechanism of reduced allograft rejection (both kidney and heart) remains unclear, it is speculated that the organ combination induces immunogenic tolerance.…”
Section: Discussionsupporting
confidence: 76%
“…Multiple single-institution studies of combined HKTx have been reported. [2][3][4]14,16,17 Raichlin and colleagues 4 compared the results of 12 patients undergoing combined organ transplantation with those of 183 patients undergoing isolated HTx at the Mayo Clinic over a 10-year period (1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007). Post-transplant survival was equivalent in both groups, as in our study described here.…”
Section: Discussionmentioning
confidence: 99%
“…These seemed to be centered around hemodynamic instability and prolonged operating time, such as prior cardiac surgery, prior heart or kidney transplant, and requirement for extracorporeal membrane oxygenation support. 40 , 41 , 42 Overall, this suggests that utilization of kidney allografts for HKTx patients is appropriate, with care taken to identify patients at increased risk of poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Needless to say, immunological advantages of a same donor organ transplantation [30] would be lost in such a concept, however, previous investigations demonstrated encouraging results on kidney after heart transplantation [31,32], with the most recent study originating from the United Network for Organ Sharing database data showing even superior patient survival in comparison to HKTx [33].…”
Section: Discussionmentioning
confidence: 99%